Complimentary Address - Koczy, Laszlo T. (Journal of advanced computational intelligence and intelligent informatics, 2017)
It is my honour and privilege to express my heartfelt congratulations to the Journal of Advanced Computational Intelligence and Intelligent Informatics (JACIII) at the occasion of its 20 th Anniversary. I was so lucky to be one of the founding Advisory Editors in 1997, invited by two excellent researchers and very close friends, now Emeritus Professors Kaoru Hirota and Toshio Fukuda, and I have been on the board ever since. The journal covers all important fields of Computational Intelligence and Soft Computing including Fuzzy Systems, Artificial Neural Networks, Evolutionary Algorithms, and others. These areas emerged since the 1960-s, but especially since the second half of the 1980-s, when the Fuzzy Boom exploded in Japan. I was able to attend the International Fuzzy Systems Association World Congress in 1987 in Tokyo, in the same year when world’s first automatic subway line was opened in Sendai and when so many domotic and other applications appeared on the market, among other fuzzy and neuro-fuzzy commercial products. This was the occasion when I made the friendship of the two outstanding scholars, who later started JACIII.From year to year I have diligently followed the articles published in JACIII, sending annually recommendations for the best paper awards, and occasionally sending papers for publication or advising my peers to support the journal. This way I can sincerely state that in the past 20 years JACIII has become one of the leading periodicals of the CI and SC fields, its authors distributed not only in Japan, but all over the world. At the beginning the focus was naturally on the fuzzy related papers, while in time the scope opened up towards all other related research fields, gradually covering all Intelligent Systems topics.Why is the mentioned research area so important? Real life problems and many commercial applications, industrial, economic, bio-medical, environmental or others often pose a challenge by the complexity of the problem that disables modeling and algorithmic solutions from the mathematical point of view. This complexity partly comes from the large number of state variables describing the inputs and outputs involved with the model, or from the undeterministic nature, the high adaptability need, or simply from the involvement of subjective elements coming from human experts, operators or other persons. To all these mathematically intractable problem classes intelligent technologies often deliver a very good answer, a good compromise of resource efficiency and modeling “goodness”, i.e. approximation accuracy, or optimality error. The articles published in JACIII during the past 20 years have given many good answers to these challenging questions, offering new methodological results and new application technics.I sincerely hope that JACIII will continue its fruitful and important activities and will play an ever increasing role in the international scenario of research publications on Intelligent Systems. Long live JACIII!